1998
DOI: 10.4037/ajcc1998.7.3.168
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the precipitants of hospitalization for heart failure decompensation

Abstract: BACKGROUND: The model for management of patients with heart failure may be a key determinant of morbidity and quality of life. Development of a better management strategy for these patients requires determination of the reasons for decompensation that leads to hospitalization. OBJECTIVES: To ascertain and rank the principal reasons for hospitalization of patients who have heart failure. METHODS: Retrospective audit of all 1992 admissions (N = 1031; 691 patients) coded for heart failure at a Veterans Affairs me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(79 citation statements)
references
References 0 publications
2
71
0
6
Order By: Relevance
“…High sympathetic nervous system activity is observed in winter, whereas cutaneous vasodilatation and loss of water and salt from sweating is the suggested mechanism for low blood pressure in summer [6]. The incidence of chronic heart failure, coronary heart disease and stroke are also highest in winter [7][8][9][10][11], and there may be a link between infection and cardiovascular disease through endothelial dysfunction and activation of the inflammatory and coagulation system [12][13][14][15][16][17]. Indeed, previous studies estimated that ∼10-20% of heart failure is attributable to respiratory disease [14][15][16], and another recent study from the USA also confirmed the association of influenza-like illness with cardiovascular mortality [17].…”
Section: Introductionmentioning
confidence: 99%
“…High sympathetic nervous system activity is observed in winter, whereas cutaneous vasodilatation and loss of water and salt from sweating is the suggested mechanism for low blood pressure in summer [6]. The incidence of chronic heart failure, coronary heart disease and stroke are also highest in winter [7][8][9][10][11], and there may be a link between infection and cardiovascular disease through endothelial dysfunction and activation of the inflammatory and coagulation system [12][13][14][15][16][17]. Indeed, previous studies estimated that ∼10-20% of heart failure is attributable to respiratory disease [14][15][16], and another recent study from the USA also confirmed the association of influenza-like illness with cardiovascular mortality [17].…”
Section: Introductionmentioning
confidence: 99%
“…In past studies of patients with HF, researchers reported variations in how medications were prescribed and issues with compliance. 39,40 Although patients reported taking medications as prescribed, a formalized monitoring system was not used. Information about dosages or changes in medications was not collected, and these variables could have differed between groups and affected results.…”
Section: Limitationsmentioning
confidence: 99%
“…Self-care is a natural decision-making process used by patients to improve their health (Riegel et al 2009a,b). Adequate self-care has been related to slowing the deterioration of disease progression, reducing readmissions (Bennett et al 1998, Yancy et al 2013 and improving the quality of life in the patients (Buck et al 2012) and their families (Vellone et al 2013). Helping patients engage in better self-care decision-making, therefore, should be the priority of nursing care.…”
Section: Introductionmentioning
confidence: 99%